Image of Ivan Terrible in European Propaganda during Livonian War (Poetic Works of S. Wolf and J. Kokhanovsky) - N. V. Eylbart (Научный диалог, 2023)
The image of Ivan the Terrible in the propagandic European poetry of the Livonian War is considered. On the example of two poetic works “An elegiac poem about the campaign of His Majesty Stephen the First, the King of Poland and the Grand Duke of Lithuania against Ivan Vasilyevich, the Grand Duke of Moscow” by the German author Samuil Wolf (1582) and “The Song of the Capture of Polotsk” by the Polish poet Jan Kokhanovsky (1580) the conclusion is made about the great interest of the European reader in the personality of the Moscow tsar. The analysis of these texts shows the grotesque image of Ivan the Terrible, formed under the influence of the “political order” coming from the Polish King Stefan Batory. It is also concluded that European propaganda played a negative role, contributed to the loss of the Muscovite state in the Livonian War. The indifference of the tsar himself to what was published about him in the West is also noted, this was the reason that Ivan the Terrible did not want to carry out reciprocal propaganda campaigns and limited himself in this regard to exculpatory and accusatory letters to S. Batory, A. M. Kurbsky and some European monarchs. “The Song of the Capture of Polotsk” was first translated into Russian by the author of the article and is published here in full.